SKEPTISME NASABAH TERHADAP KLAIM SYARIAHDARI PERBANKAN SYARIAH DI INDONESIA - Riza, Alex Fahrur (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2017)
This study aims to examine the factors that affect level of skepticism of Islamic bank customers where researchers try to see the paradigm of thinking and consumer attitude using the perspective of Theory of Reason Action (TRA)from Ajzen and Fishbein (1980). The survey was conducted on 597 Islamic bank customers using a Google form distributed online. All hypotheses proposed in this study are supported. These results show that in the context of Islamic banking in Indonesia, researchers find that the level of skepticism will decrease as customers better understand the information received and evaluate information according to their needs and according to their expectations. Researchers try to contribute both practically and theoretically.First, practically this research provides important information for practitioners that customers still have a skeptical attitude towards sharia claims from Islamic banking. Finally, theoretically this study contributes to the literature by testing the skepticism of Islamic banking customers which is still a research gap in marketing research and consumer behavior in general and the research of sharia banking in particular.